Business cycles in reunified Germany: closer together or further apart? - Ferreira-Lopes, A.; Sequeira, T. N. (Review of Urban and Regional Development Studies, 2011)
In this article we document the features of business cycles in German states from 1970 and 2009. Specifically, we answer the question if German states are becoming more synchronized or not. All results indicate that the synchronization of cycles is stronger inside the former Western Germany and inside the former Eastern Germany. The reunification process has had a strong influence in terms of business cycle association. However, a process of cyclical convergence has begun, although slowly, after the reunification.